1998
DOI: 10.1111/acer.1998.22.s3_part1.97s
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Platelet Membrane Lipid Compositions and Platelet Aggregability in Alcoholic Liver Disease

Abstract: We studied the relationship between changes in platelet aggregability and platelet membrane lipid in alcoholic liver disease. The maximal rate of ADP‐induced platelet aggregation was significantly increased in the alcoholic liver disease group than in the control group. No significant difference was observed in the maximal rate of collagen‐induced platelet aggregation. However, a lag time required for the start of platelet aggregation was significantly shortened in the alcoholic liver disease group, indicating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Defective platelet aggregation and reduced platelet production of thromboxane-A2, a metabolite of arachidonic acid, are common findings in patients with cirrhosis [30], along with storage pool deficiency and abnormalities of the platelet GPIIb [31,32] Although both free cholesterol and phospholipids in platelet membranes are increased and palmitic acid is decreased in alcoholic liver disease, no significant changes in arachidonic acid has been observed [33]. Elevated platelet-activating factor (PAF) levels were found in human cirrhotic livers when compared with noncirrhotic tissues, thus confirming previous results obtained in experimental animal models of cirrhosis [34,35].…”
Section: Acquired Hemostatic Abnormalities In Liver Diseasesmentioning
confidence: 99%
“…Defective platelet aggregation and reduced platelet production of thromboxane-A2, a metabolite of arachidonic acid, are common findings in patients with cirrhosis [30], along with storage pool deficiency and abnormalities of the platelet GPIIb [31,32] Although both free cholesterol and phospholipids in platelet membranes are increased and palmitic acid is decreased in alcoholic liver disease, no significant changes in arachidonic acid has been observed [33]. Elevated platelet-activating factor (PAF) levels were found in human cirrhotic livers when compared with noncirrhotic tissues, thus confirming previous results obtained in experimental animal models of cirrhosis [34,35].…”
Section: Acquired Hemostatic Abnormalities In Liver Diseasesmentioning
confidence: 99%
“…Smeets et al also found cholesterol to increase the activity of lipid vesicles, with a composition mimicking the outer leaflet of the plasma membrane of the activated platelet (16). Further support is provided by Watanabe et al, who showed that among patients with alcoholic liver disease, increased cholesterol in platelet membranes correlates with hyperaggregation (17). We hypothesize that although patients with spur cell anemia have advanced liver disease with low production of extrinsic pathway clotting factors, they may actually be hypercoagulable, causing an absence of bleeding despite elevation of the PT-INR.…”
Section: Discussionmentioning
confidence: 91%
“…The present results suggest that platelet hypoaggregability might be induced in smokers and alcoholics by γ - and β -carbolines. However, the influences of cigarette smoking and alcohol consumption on platelet aggregation have been conflicting, with some studies reporting a reduction of aggregability [ 1 7 ] but others an enhancement of aggregability [ 8 11 ]. In contrast to fluid membranes (with increased fluidity) induced by AD γ C and AM γ C, rigid membranes (with decreased fluidity) show the enhanced platelet aggregability in response to epinephrine and thrombin [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the enhanced platelet aggregability could be found in chronic smokers, subjects who had smoked 10 ± 2 cigarettes per day for 7–10 years showed the decreased fluidity of platelets, which was due to an increase of cholesterol in platelet membranes [ 58 ]. Platelet aggregability in response to ADP and collagen was enhanced in alcoholics with increasing cholesterol in platelet membranes [ 11 ]. The conflicting phenomena, hypoaggregability and hyperaggregability, associated with cigarette smoking and alcohol consumption appear to be explained by the biphasic effects of membrane fluidity changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation